A 2-Year Retrospective Case Series on Isolates of the Emerging Pathogen Actinotignum schaalii from a Canadian Tertiary Care Hospital - Pramath Kakodkar; Camille Hamula (Microorganisms, 2022)
(1) Background: Actinotignum schaalii is an emerging, opportunistic pathogen often linked with UTIs but can extend beyond the urogenital system. Data on the clinical significance of A. schaalii are still emerging. (2) Methods: A retrospective review of A. schaalii isolates in a Canadian tertiary care hospital was conducted. The clinical data of patients that grew A. schaalii from January 2020 to 2022 were documented. Demographics, site, management, and microbiological parameters surrounding culture and sensitivities were recorded. (3) Results: A total of 43 cases of A. schaalii were identified. Actinotignum schaalii was primarily involved in UTIs (n = 17), abscesses (n = 9), bacteremia (n = 6), septic arthritis (n = 5), and ulcers (n = 5). A. schaalii had a slight predilection for polymicrobial infections (51.1%, n = 22 out of 43), with Aerococcus urinae (n = 5) being the most common coisolate. Susceptibility testing was only performed in two cases that showed sensitivity to beta-lactam antibiotics and resistance to metronidazole and ciprofloxacin. Amoxicillin–clavulanate (n = 5) is the most frequently prescribed antibiotic. (4) Conclusions: The non-urogenic clinical significance of A. schaalii remains undervalued. The management of A. schaalii infection is multimodal, consisting predominantly of antimicrobials and surgical procedures specific to the etiology. Clinicians should request sensitivities for A. schaalii so that appropriate antimicrobial coverage can be provided.